MESSAGE REPLY METHOD AND APPARATUS, AND ELECTRONIC DEVICE - WANG, Xingcan (2022)
Disclosed are a message reply method and apparatus, and an electronic device. The message reply method comprises: upon receiving M messages from N contacts, receiving a first input from a user, wherein one contact corresponds to at least one message, and M and N are integers greater than 1; in response to the first input, displaying K identifiers, wherein one identifier indicates one contact, and K is an integer greater than 1; receiving a second input from the user; in response to the second input, sending a reply message to an electronic device of a target contact indicated by a target identifier in the K identifiers, wherein the target identifier is at least one identifier in the K identifiers. Sont divulgués un procédé et un appareil de réponse à un message, ainsi qu'un dispositif électronique. Le procédé de réponse à un message consiste à : lors de la réception de M messages à partir de N contacts, recevoir une première entrée d'un utilisateur, un contact correspondant à au moins un message, et M et N ét